RISK FACTORS OF PHANTOM LIMB PAIN IN PATIENTS WITH LOWER LIMB AMPUTATIONS - Jelčić, Sandra (Acta medicae Medianae, 2026)
Phantom pain is a common and complex complication following limb amputation. Current pharmacological, psychological, and rehabilitative approaches are only partially effective, indicating the need for further research.This study aimed to examine risk factors associated with the occurrence of phantom pain in patients with lower limb amputations.A cross-sectional study was conducted at the Clinic of Medical Rehabilitation of the University Clinical Center of Vojvodina in Novi Sad, including 53 patients with acquired lower limb amputation in either the pre-prosthetic or prosthetic phase of rehabilitation. Data were collected from medical records and patient history regarding age, sex, presence of cardiovascular comorbidities, diabetes mellitus, various types of pain, body mass index, level of amputation, and characteristics of the residual limb. Statistical analysis was performed using JASP software, applying descriptive statistics, the Student’s t-test, the χ² test, and binary logistic regression to examine factors associated with the occurrence of phantom limb pain. Statistical significance was set at p < 0.05.Phantom limb pain was reported in 16 patients (30.18%). A statistically significant association was found between phantom pain and the level of amputation (p = 0.046), as well as the phase of rehabilitation (p = 0.011).The level of amputation and the phase of rehabilitation represent significant risk factors for the development of phantom limb pain.
Keywords: phantom pain, lower limb amputation, diabetes mellitus